Enhancing interlaminar fracture characteristics of woven CFRP prepreg composites through CNT dispersion - Joshi, Sunil Chandrakant (2013)
The inter-ply characteristics of polymeric prepreg composites influence their interlaminar fracture toughness and the overall performance. This article embarks on engineering the inter-ply interfaces of carbon fiber reinforced polymer (CFRP) composites. A novel and practical technique for dispersion of multi-walled carbon nanotubes (MWCNTs) onto woven CFRP prepreg is presented. The interlaminar fracture toughness of these CFRP lay-ups was evaluated experimentally and compared with the regular (without any CNTs) specimen. Double cantilever beam and end notch flexure tests were conducted for interlaminar fracture studies. It was observed that the addition of MWCNTs in between the CFRP prepreg plies helps in strengthening the interface. There existed an optimum percentage in which these nanofillers should be added. The presence of nanotubes increased fiber bridging within the ply interfaces, which in turn controlled the inter-ply crack propagation. The findings and the mechanisms are discussed using the test data, SEM pictures, schematics, and scans of the fractured surfaces.